The interaction between donors and recipients: A case study on Egypt's bilateral aid regime - Mashhour, Salma (AUC Knowledge Fountain, 2016)
“Before, during, and after the Arab Spring, one thing has remained constant in the Middle East: the outsized influence of outside powers. ” Financial aid is one form of this influence that is allocated to different countries in a variety of forms; it is subsequently used in a variety of ways. The literature on aid effectiveness has reached divergent conclusions, calling for a new way of assessing the impact of aid and conditionality on a government. As such, the impact of aid on the government in Egypt is observed as a stabilizing factor and donor policies seem to be resilient despite changes in global constellations and threats at various periods of time to withdraw the aid, and despite the diversity of donors and their conditions-if any. The literature to this point fails to explain the relevance of aid on government type and characteristics; accordingly, it fails to explain the interaction between donor conditions and recipient actions; whether this resilience is explained by weak measures and de-facto conditionality or by the strength of the recipient government. Donors, however, are not uniform; they exhibit strikingly disparate aims and conditions attached to their allocation of aid. Therefore, they must be assessed in two different groups: Western donors and Non-Western donors. In this sense, as will be shown in the literature review, aid has been assessed in a way that has lead to divergent conclusions that fail to explain the extent of the effect of aid on stabilizing the existing government in Egypt. With the emergence of new donors in the international aid system and with the apparent resilience of the Egyptian government and its various characteristics, the role of aid in this becomes questionable. In this sense, this thesis will adopt a new method on assessing the impact of aid on government characteristics by observing the interaction between donors and recipients, in an attempt to explain the effect of aid on the Egyptian government.